Bio-acoustic signaling; exploring the potential of sound as a mediator of low-dose radiation and stress responses in the environment. (3rd June 2022) - Matarèse, Bruno F. E.; Lad, Jigar; Seymour, Colin; Schofield, Paul N.; Mothersill, Carmel
Abstract: Objectives: This commentary reviews and evaluates the role of sound signals as part of the infosome of cells and organisms. Emission and receipt of sound has recently been identified as a potentially important universal signaling mechanism invoked when organisms are stressed. Recent evidence from plants, animals and microbes suggests that it could be a stimulus for specific or general molecular cellular stress responses in different contexts, and for triggering population level responses. This paper reviews the current status of the field with particular reference to the potential role of sound signaling as an immediate/early bystander effector (RIBE) during radiation-induced stress. Conclusions: While the chemical effectors involved in intercellular and inter-organismal signaling have been the subject of intense study in the field of Chemical Ecology, less appears to be known about physical signals in general and sound signals in particular. From this review we conclude that these signals are ubiquitous in each kingdom and behave very like physical bystander signals leading to regulation of metabolic pathways and gene expression patterns involved in adaptation, synchronization of population responses, and repair or defence against damage. We propose the hypothesis that acoustic energy released on interaction of biota with electromagnetic radiation may represent a signal released by irradiated cells leading to, or complementing, or interacting with, other responses, such as endosome release, responsible for signal relay within the unirradiated individuals in the targeted population.